A review, analysis and extension of water activity data of sugars and model honey solutions. (1st October 2020) - Subbiah, Balaji; Blank, Ursula K.M.; Morison, Ken R.
Highlights: Water activity data for glucose, fructose, maltose and glycerol were reviewed. Calculated hydration numbers were very sensitive to uncertainties in water activity data. A multi-component extension was proposed and tested for prediction of water activity. The water activity of model honey solution was predicted with good accuracy. Abstract: Water activity is a physical property measured in the food industry which helps predict shelf life and microbial activity. Honey normally has a water activity less than 0.6, but this can vary with the amount of crystallization in solution. The aim of this work was to obtain relationships, as fundamental as possible, that can be used to predict the water activity of solutions with compositions similar to honey. Water activity measurements of aqueous sucrose solutions have been well analysed in literature using hydration theory. The analysis based on hydration numbers was easily able to show the quality of data previously published, and hence relationships were proposed for the hydration numbers of glucose, fructose, maltose and glycerol. A model was proposed in this study, to predict the water activity of food systems containing high concentrations of sugars and some electrolytes. The model was analysed and validated using mostly literature data supplemented with new experimental data.